2008
DOI: 10.1073/pnas.0808649105
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelium contributes to vascular smooth muscle and mesenchyme during lung development

Abstract: During mouse development, the sophisticated vascular network of the lung is established from embryonic day (E)Ϸ10.5 and continues to develop postnatally. This network is composed of endothelial cells enclosed by vascular smooth muscle, pericytes, and other mesenchymal cells. Recent in vivo lineage labeling studies in the developing heart and intestine suggest that some of the vascular smooth muscle cells arise from the surface mesothelium. In the developing lung, the Wilm's tumor 1 gene (Wt1) is expressed only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 233 publications
(205 citation statements)
references
References 29 publications
11
193
1
Order By: Relevance
“…These were not specifically identified and could have been alveolar myofibroblasts, microvascular pericytes, or even endothelial cells (Que et al, 2008). This finding warrants further investigation, preferably with an inducible Cre line, to identify all of the mesothelial-derived cells and the developmental stage at which they are produced; moreover, to determine how many different progenitor populations the embryonic lung mesothelium contains and whether any of these also function in the adult.…”
Section: Other Mesenchymal Progenitor Populationsmentioning
confidence: 96%
See 2 more Smart Citations
“…These were not specifically identified and could have been alveolar myofibroblasts, microvascular pericytes, or even endothelial cells (Que et al, 2008). This finding warrants further investigation, preferably with an inducible Cre line, to identify all of the mesothelial-derived cells and the developmental stage at which they are produced; moreover, to determine how many different progenitor populations the embryonic lung mesothelium contains and whether any of these also function in the adult.…”
Section: Other Mesenchymal Progenitor Populationsmentioning
confidence: 96%
“…lineage-tracing experiments in the lung demonstrated that the mesothelium contributes $30% of the vascular smooth muscle in both arteries and veins, but that it makes no contribution to the parabronchial smooth muscle (Que et al, 2008;Morimoto et al, 2010;Fig. 5).…”
Section: Vascular Smooth Muscle Progenitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…into pregnant female mice at E12.5 and E13.5. Smad4 flox/flox and Rosa26R-CAG-STOP-hPLAP mice (Rosa PLAP ) have been described previously (24,25). All experiments were conducted according to protocols approved by the Duke University Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we assessed axonal outgrowth in vivo by examining the projections of trigeminal axonal collaterals using the Rosa PLAP reporter line (24,25). No apparent differences were detected in the growth of sensory axonal collaterals into brainstem nuclei between control and mutant mice in embryonic and postnatal stages (Fig.…”
Section: Generation Of Mice With Impaired Tgf-β Signaling In Sensory mentioning
confidence: 99%